Testing the Psychometric Properties of the Challenging Parent Standard Questionnaire (CPSQ) in the Italian Educational Context - Pepe, Alessandro; Addimando, Loredana (International Journal about Parents in Education, 2023)
The Challenging Parent Standard Questionnaire (CPSQ) is a measurement tool aimed at surveying the field of parent-teacher relationships to assess the frequency of challenging parental behaviours as well as the occupational stress experienced by teachers in response to those behaviours.The present study examined the factor structure and the main psychometric properties of the CPSQ in a sample of Italian in-service primary and lower secondary teachers (N = 1,025). In order to investigate the most appropriate factor structure for the Italian version of the questionnaire, researchers compounded three different factor retention methods: K1 rule (Kaiser, 1960), scree test (Cattel, 1966) and parallel analysis (Horn, 1965).The results show a practical and robust five-factor measurement model describing the challenging behaviours of parents: ‘Excessively worried about education’, ‘Unsatisfied’, ‘Uncooperative’, ‘Overprotective’ and ‘Uninvolved’.In Italian primary and lower secondary schools, the CPSQ factor pattern partially differs from the pattern found in studies conducted in different educational contexts (i.e., Lambert & McCarthy, 2006; Van der Wolf & Everaert, 2005). Recommendations for a more accurate factor retention process in testing factorial invariance in measurement tools are discussed.